Phonological Process of Japanese Affricates [dz] and [ts] of Javanese Native Speakers - Shinohara, Misaki; Subiyanto, Agus (Vocational College of Diponegoro University, 2023)
Indonesia now has the second largest number of Japanese language learners in the world after China. Among those many learners, there are those who use the Japanese language in part of their lives by working and studying in Japan, or working at Japanese companies in Indonesia. In Japanese language education, the aim is to teach learners to be able to communicate correctly with Japanese people. In order to communicate correctly, it is essential to remember words and learn the correct structure of sentences, but phrasing is also necessary for comfortable conversation. Pronunciation and accent accuracy are also very important in these verbal communications. It is common for learners to be misunderstood due to mistakes in pronunciation or accent, or to have trouble understanding what they are saying to Japanese people. Pronunciation and accent articulation can be tricky. At times, many learners do not notice the difference in sounds, or cannot move their mouths and tongues according to Japanese pronunciation. The reasons for this difficulty include the features of Japanese that are not found in other languages as well as the mother tongue interference. There are some Japanese pronunciations that are not in their native language. Learners often replace such unknown Japanese phonemes with familiar pronunciations. Its pronunciation is chosen from among mother tongues. Indonesia is a multiethnic and multilingual country. Among them, Javanese is spoken by a lot of people in Indonesia. There are some characteristics in the pronunciation of Japanese learners whose mother tongue is Javanese, and it is believed that these characteristics are related to their mother tongue. Japanese has affricates [dz] and [ts]. These affricates are said to be pronunciations that many Japanese learners around the world find difficult. Javanese native speakers also have difficulties to make [dza], [dzɯ], [dze], [dzo], and [tsɯ], correctly. Analysing learners’ phonological processes and the cause of this phonologically. This research will provide hints for improving the pronunciation of Javanese native speakers.